Peningkatan Hasil Belajar Siswa Kelas X IPS 1 dalam Pembelajaran Seni Tari Melalui Metode Jigsaw di SMA Negeri 1 Kerinci Tahun Pelajaran 2019/2020 - Ning Ayuni (Universitas Batanghari Jambi, 2021)
This research was a classroom action research. The research objective was to improve the student’s achievement on Dancing Art subject by using Jigsaw method. The research participant was the students at grade X IPS 1 SMAN 1 Kerinci consisted of 20 students. The research was done in two cycles which had four phases (1) Planning (2) Action (3) Observation (4) Reflection. The data were collected by using observation, performance test, documentation, interview and questionnaire. The instruments of the research were field note, observation sheet, research sheet, interview guide, and Questionnaire. The analysis result showed that the student’s learning activeness during the two cycles improved. It could be seen from the improvement of the student’s activeness level. It was observed from their well enthusiastic and cooperative team work in forming dancing moves and floor pattern, the students were able to gather the dancing moves into a dancing creation, and they were performing both things confidently. The improvement in achievement was seen from the quantitative data that there were 5 students (25%) who got 75 in pre-cycle. It went better when Jigsaw method was implementd in cycle 1 and 2. There were 12 students (60%) who got achieved score, and 8 of them (40%) who got unachieved score in the first cycle. Then, the next cycle showed that there were 17 students (85%) who got achieived score and 3 of them (15%) who were at unachieved level. It concluded that Jigsaw method improved the student’s achievement in Dancing Art Subject.